Comparison of the Radiologic, Morphometric, and Clinical Outcomes between Kinematically and Mechanically Aligned Total Knee Arthroplasty: A Propensity Matching Study - Kim, Tae Woo; Lee, Jae Ik; Choi, Han Gyeol; Yoo, Hyun Jin; Kim, Kyu Tae; Lee, Yong Seuk (The Journal of Knee Surgery, 2021)
The purpose of this study was to compare radiologic, morphometric, and clinical outcomes between kinematically aligned (KA) and mechanically aligned (MA) total knee arthroplasty (TKA) in Korean patients. Overall, 168 patients who underwent primary TKA were retrospectively reviewed, and propensity matching (age, sex, and body mass index) was performed as 1:3 ration (KA TKAs [n = 42]: MA TKAs [n = 126]). Joint-line orientation angle (JLOA), coronal and axial alignments of implants, hip–knee–ankle (HKA) angle, and patellar tilt angle were assessed using full-length standing radiograph, axial computed tomography (CT) scan, and plain radiographs. Morphometric assessment was performed by analyzing the intraoperative measurement of the femoral cut surface and femoral components fitting in five zones. Clinical outcomes more than 2 years of follow-up were evaluated with the Knee Society (KS) knee and functional scores, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores, and the Short-Form Health Survey (SF-36). In radiologic results, JLOA was more parallel to the floor in KA TKAs (KA: medial tilt 0.9 ± 1.5 degrees; MA: lateral tilt 1.7 ± 1.5 degrees, p < 0.05), and patellar tilt angle was closer to preoperative status after KA TKA (KA: 2.0 ± 1.6 degrees; MA;0.3 ± 1.2 degrees, p < 0.05). HKA angle and rotational mismatch were similar between two groups. In morphometric analysis, entire overhang of anterior femoral cutting surface was reduced in KA TKA compared with MA TKA (KA: 11.7 ± 6.2 mm; MA: 14.4 ± 5.9 mm, p < 0.05). However, both of MA and KA TKAs showed underhang in mediolateral dimension without difference. There were no significant differences in clinical scores between two groups. KA TKA showed more parallel JLOA to floor, closer patellar tilt to preoperative status, and better anterior flange fitting that can reproduce more natural knee kinematics compared with MA TKA. Although clinical outcomes assessed by conventional evaluating tools were similar between two groups, further evaluation focusing on the patellofemoral symptoms or unawareness of TKA is necessary to clarify the clinical benefit of KA TKA.
Keywords: total knee arthroplasty; kinematic alignment; mechanical alignment; coronal alignment; rotational alignment; morphometry